Evaluation of thyroid function and metabolic parameters in obese and overweight children: A prospective case-control study - GÜRAN, TÜLAY (My University, 2022)
Obesity is considered an important global public health challenge, and its prevalence is rapidly increasing in children. We investigated in this study if the upper-normal TSH level may be associated with metabolic syndrome parameters, including obesity, high blood pressure, and dyslipidemia and changes in insulin sensitivity in overweight and obese children. We also investigated whether there is a relationship between BMI and these parameters. This prospective case-control study comprised 145 participants (74 females, 71 males) aged 5-18 years. Participants were divided into three groups according to their BMI z-score, as overweight, obese and control. The control group included 35 age and sex-matched healthy subjects. Thyroid stimulating hormone levels of control, overweight and obese groups were 2.14 +/- 1.27, 2.97 +/- 1.26 and 3.13 +/- 1.11, respectively (p<0.05). There was a significant positive correlation between TSH and the BMI, BMI z-scores between overweight and obese groups (r=0.302, p=0.000), (r=0.121, p=0.004), respectively. The current study suggests that increased serum TSH levels, even within the normal range, in overweight and obese children is associated with the impairment of metabolic parameters, including dyslipidemia and insulin sensitivity. For that reason, TSH levels in the high-normal range should be considered as a risk factor for metabolic syndrome and its components.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); İncelemeler ve Referanslar (tıbbi); Araştırma ve Teori; Reviews and References (medical); Research and Theory; body mass index; insulin; metabolic parameters; obesity; thyroid hormone; STIMULATING HORMONE-LEVELS; BODY-MASS INDEX; SERUM-LIPID CONCENTRATIONS; INSULIN-RESISTANCE; REFERENCE RANGE; THYROTROPIN LEVELS; ASSOCIATION; POPULATION; TSH; HYPOTHYROIDISM